Impact of measurement error in the study of sexually transmitted infections. Issue 4 (4th August 2004) - Myer, L; Morroni, C; Link, B G
Abstract : Measurement is a fundamental part of all scientific research, and the introduction of errors of different sorts is an inevitable part of the measurement process in epidemiological and clinical research. Despite the ubiquity of measurement error in research, the substantial impacts which measurement error can have on data and subsequent study inferences are frequently overlooked. This review introduces the basic concepts of measurement error that are most relevant to the study of sexually transmitted infections, and demonstrates the impacts of several of the most common forms of measurement error on study results. A self assessment test and MCQs follow this paper.